The UCF Report, Vol. 22 No. 3, August 27, 1999 (1999)
Enrollment could approach 32,000: More students than ever are ate tending UCF this semester, and enrollment is expected to grow to 48,000 by 2010; Athletics complex is field of dreams: Build stadiums and a bigger arena, and major conference, more fans will come; Sharp student receives UCF's 100,000th degree: Chris Sharp's college career began on a dare; now, he has a master's degree